Five-minute activities : a resource book of short activities - Ur, Penny; Wright, Andrew, 1937- (New York : Cambridge University Press, 1992)
Contains over one hundred thirty five-minute activity lessons designed to supplement regular English instruction in order to learn or practice a particular concept or provide a transition between lessons.
Includes bibliographical references (p. 102) and index.
Adult
Keywords: Activity programs in education; Language arts (Elementary); Activity programs in education; Language arts